Connective tissue dysplasia as a predictor of premature skin aging - Nikolai N. Potekaev; Olga B. Borzykh; Elena I. Karpova; Marina M. Petrova; Natalia A. Shnayder; Diana V. Dmitrenko; Maria A. Zatolokina; Olga M. Demina (Russian Open Medical Journal)
Background — One of the manifestations of connective tissue dysplasia (CTD) is premature skin aging. The latter can have different etiological factors. The objective of our study was to investigate the effect of predictors of premature skin aging, especially CTD, on the severity of involutional changes in the skin, as well as to develop the approach for the management of patients with premature aging. Material and Methods — We included in our study 78 women 35-45 years of age with no substantial anti-aging treatment procedures in their anamneses. We considered genealogical and cosmetological anamneses, and life history (including somatic pathology), physical examination; determined prevailing type of facial skin aging; identified predictors of CTD, assessed psychoemotional state of the patient, and performed sonography of the skin and biochemical examination of patient serum. At a clinical stage, we conducted a randomized comparative study of biorevitalizant efficacy in patients with normal and premature patterns of skin aging. Results — Our study established the role of CTD in assessing the risk of premature skin aging. In addition to the presence of CTD, the importance of identifying isolated phenotypic manifestations of CTD (such as arachnodactyly, hypermobility syndrome, low relative weight of the patient, and skin manifestations of CTD) was shown. Other predictors were also analyzed; their identification can help assessing the risk of premature skin aging. Among them, somatic pathology (varicose veins, herniated discs, visceroptosis, autonomic vascular dystonia) and physical examination data (such as pallor of the facial skin, swelling, skin hyperelasticity) were noted. When assessing the clinical efficacy of biorevitalization, the greatest satisfaction of patients with premature skin aging regarding its results was characteristic for the group of patients after 7% collagen treatment. The clinical efficacy according to sonography and histological examination in patients with premature skin aging was significantly higher after the use of collagen or a complex hyaluronic acid (HA) preparation, compared with native HA. Patients with premature skin aging exhibited high level of anxiety and/or depression, which in turn increased the risk of underestimating the outcome of procedures. Conclusion — The presented study confirmed the role of CTD in assessing the risk of premature skin aging. Predictors were revealed (somatic pathology, type of facial aging, physical examination data of the patient, etc.) that could be used to assess the risk of premature skin aging. In patients with premature aging, preparation with native HA (as a biorevitalizant) had a low clinical efficacy comparable to using placebo. A collagen-based preparation and a complex HA-based preparation exhibited high clinical efficacy. Also, patients with premature aging of the skin had a higher score of anxiety and depression, while patients with high levels of anxiety and depression were more likely to underestimate the satisfaction with the results of their aesthetic treatment.